Description of a species of the genus Cheylostigmaeus Willmann (Acari: Stigmaeidae) from Eksisu Marsh, Turkey - Dogan, Salih; Dilkaraoglu, Sibel; Fan, Qing-Hai; Sevsay, Sevgi; Erman, Orhan; Adil, Sezai (Systematic & Applied Acarology Soc London, Natural History Museum, 2015)
The discovery of both sexes of Cheylostigmaeus variatus sp. nov. from grassy soil at Eksisu marsh in Turkey adds more data to our knowledge of this genus. We herein describe and illustrate it and also provide a key to the known species in Turkey.
Keywords: Raphignathoid Mites Acari; Iran; Trombidiformes; Checklist; Fauna